2022
DOI: 10.4103/jfmpc.jfmpc_1366_21
|View full text |Cite
|
Sign up to set email alerts
|

Peppermint drop effect on ileus following cesarean section

Abstract: Objective: Intestine dysfunction and ileus are one of the cesarean section complications. medicinal herbs have been used to restore the postoperative intestinal function. Therefore, we decided to use a mint drop to improve bowel function after cesarean section. Methods and Materials: 102 women enrolled in the study. The patients were simply randomized and double blindly divided into two groups of 51 patients and giving them medication (mint drops) or placebo. Then, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Cesarean section introduces a substantial volume of blood and amniotic fluid into the peritoneal cavity, requiring abdominal cavity cleaning, which can trigger intestinal disorders, 2 and consequently pain, abdominal distension, and difficulties in initiating adequate breastfeeding. 3 Previous research has demonstrated that early feeding post-cesarean section, by mitigating nausea and vomiting and promoting more frequent bowel movements, plays a vital role in the recovery of patients. 4 …”
mentioning
confidence: 99%
“…Cesarean section introduces a substantial volume of blood and amniotic fluid into the peritoneal cavity, requiring abdominal cavity cleaning, which can trigger intestinal disorders, 2 and consequently pain, abdominal distension, and difficulties in initiating adequate breastfeeding. 3 Previous research has demonstrated that early feeding post-cesarean section, by mitigating nausea and vomiting and promoting more frequent bowel movements, plays a vital role in the recovery of patients. 4 …”
mentioning
confidence: 99%